2015
DOI: 10.1098/rspa.2015.0231
|View full text |Cite
|
Sign up to set email alerts
|

Peridynamic simulations of brittle structures with thermal residual deformation: strengthening and structural reactivity of glasses under impacts

Abstract: In glass research, the effect and influence of pre-deformation by thermal or chemical treatment is of great importance when configuring different mechanical properties or scratch resistance on the surface of glasses. In particular, such pre-deformation affects dynamic fracture or damage evolution when glass structures are under impact or collision conditions. Peridynamics provides a seamless approach for the simulation of dynamic damage evolution of the system under aggressive environments. Revising the pair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A detailed description of this can be found in the relevant literature [ 44 ]. Scaled fracture energy is noted to affect the crack speed in some studies [ 50 ] because no damping and no friction is included in the interactions between damaged material points. However, the damage results are not affected by the mesh size [ 51 ].…”
Section: Numerical Analysis and Validationmentioning
confidence: 99%
“…A detailed description of this can be found in the relevant literature [ 44 ]. Scaled fracture energy is noted to affect the crack speed in some studies [ 50 ] because no damping and no friction is included in the interactions between damaged material points. However, the damage results are not affected by the mesh size [ 51 ].…”
Section: Numerical Analysis and Validationmentioning
confidence: 99%
“…24 The current work uses peridynamics, a non-local theory of continuum mechanics to investigate microstructural mechanisms of toughening. 25 Although peridynamics has been applied in the past to study glass and ceramic fracture at the macroscale, [26][27][28][29] the application to microscale simulations has been limited. Some work has been done on polycrystalline brittle materials, [30][31][32][33] carbon fiber composites, [34][35][36][37] nanocomposites, [38][39][40][41][42] metal matrix composites, 43,44 and polycrystalline metals.…”
Section: Introductionmentioning
confidence: 99%
“…Peridynamics simulation 23,24 is a macroscale numerical method used to evaluate damage in brittle materials such as window glass. [25][26][27][28] It was used to confirm our hypothesis that the lower "effective" modulus results in a higher resistance against crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies by means of molecular dynamics (MD) 21,22 have examined the mechanical properties of the composite glass and indicated that the metal nanoparticles decrease the elastic modulus by increased ductility due to the lower yield strength and higher plasticity. Peridynamics simulation 23,24 is a macroscale numerical method used to evaluate damage in brittle materials such as window glass 25‐28 . It was used to confirm our hypothesis that the lower “effective” modulus results in a higher resistance against crack initiation.…”
Section: Introductionmentioning
confidence: 99%